The Perception of English Language Teachers of the Importance of E-Learning Platforms in Hebron Governorate and Yatta Governorate - Bhais, Remah Ali; Arman, Ibrahim Moh’D; Abu Tair, Awni Moh’D (Journal of Educational and Psychological Sciences, 2023)
This study aimed to identify the awareness of English Language Teachers in Hebron Governorate of the Importance of E-Learning Platforms and its Relationship to their Cognitive flexibility – the researcher adopted the descriptive correlation approach on a stratified random sample،which included (262) teachers from Yatta education directorate and from south Hebron directorate،during the first semester in (2021/2022), The researchers set up a questionnaire to measure the Awareness Of English Language Teachers in Hebron Governorate of the Importance of E-Learning Platforms consisting of (30) Paragraphs. the instruments va0lidity and reliability were both verified،the reliability coefficient of the first instrument is (0.95), The results show that the Awareness of English Language Teachers in Hebron Governorate of The Importance Of E-Learning Platforms were moderate with an average of (3.55)،The results also revealed that there are no statistically significant differences in the awareness of English Language Teachers in Hebron Governorate of The Importance of E-Learning Platforms attributed to the variables of gender،educational qualification،directorate and stage) while there were differences according to the variable (years of experience).
Keywords: E-Learning; Perception; Platforms